ACEH FRIED SAMBAL BUSINESS DEVELOPMENT STRATEGY DURING THE COVID-19 PANDEMIC IN GAMPONG MEUNASAH LHOK MEUREUDU DISTRICT PIDIE JAYA DISTRICT - Ori Damayanti; Setia Budi; Irada Sinta (LPPM Universitas Malikussaleh - Indonesia, 2024)
The development of agricultural-based industries is very strategic to be used as the government of Indonesia. Because this industry generally relies on agricultural resources that are not durable, easy, and seasonal. Agroindustry has a strategic role in efforts to fulfill basic needs, expansion of employment opportunities, domestic production empowerment, foreign exchange acquisition and improvement in the economy of the people in the countryside. This research aims to formulate a development strategy that can be implemented or carried out by Usaha Aceh Sambal Goreng in Meunasah Lhok Village, Meureudu District, Pidie Jaya Regency. Data used in the form of primary data and secondary data. The data analysis method used is a qualitative descriptive method, then the formulation of the strategies using SWOT analysis, the results of the study show that the Usaha Aceh Sambal Goreng has the strength and opportunity to be developed. Based on the results of the SWOT diagram analysis, the value of X > 0 is 1.65 and Y > 0 is 0.78. the position of the business based on the SWOT matrix is in the quadrant 1. The results of the SWOT matrix analysis produce 9 alternative strategies.